Determinants of Finnish-Russian economic relations - Markku Kotilainen (The Research Institute of the Finnish Economy (ETLA), 2007)
The broad context of the study is the main determinants of Finnish-Russian economic relations during the post-Soviet era and the prospects for the future. The study explores the determination of trade as well as foreign direct investment (FDI). The main emphasis is on the structure and development of foreign trade. When measured by the Grubel-Lloyd index of intra-industry trade (SITC3, 4-digit), it is seen that less than 3 per cent of Finnish-Russian trade occurred inside the same industry in 2004. This percentage has even declined slightly during the period studied. In Finland's trade with Germany, the corresponding figure was 31 per cent and in trade with Sweden 47 per cent in 2004. When assessing the development of Finnish imports from Russia, we notice that the dominance of changes in oil prices and of imports of big companies does not allow sensible econometric explanations. In the case of Finnish exports to Russia we find econometric evidence on volumes and values, on aggregate and sectoral, and on annual and quarterly exports. We present several kinds of classifications of FDI, and ask which factors favour exports and which FDI. We also classify the investments of Finnish firms in Russia according to these criteria – in a very illustrative and preliminary way. Exports as well as FDI have profited from the high market growth and rapid structural change of the Russian economy.
Keywords: F14; F21; F23; 330; Finland; Russia; economic relations; foreign trade; foreign direct investment (FDI); Internationale Wirtschaftsbeziehungen; Außenhandel; Direktinvestition; Finnland; Russland